If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Simplifying v^{2}+ 7v + -8 = 0 Reorder the terms: -8 + 7v + v^{2}= 0 Solving -8 + 7v + v^{2}= 0 Solving for variable 'v'. Factor a trinomial. (-8 + -1v)(1 + -1v) = 0## Subproblem 1

Set the factor '(-8 + -1v)' equal to zero and attempt to solve: Simplifying -8 + -1v = 0 Solving -8 + -1v = 0 Move all terms containing v to the left, all other terms to the right. Add '8' to each side of the equation. -8 + 8 + -1v = 0 + 8 Combine like terms: -8 + 8 = 0 0 + -1v = 0 + 8 -1v = 0 + 8 Combine like terms: 0 + 8 = 8 -1v = 8 Divide each side by '-1'. v = -8 Simplifying v = -8## Subproblem 2

Set the factor '(1 + -1v)' equal to zero and attempt to solve: Simplifying 1 + -1v = 0 Solving 1 + -1v = 0 Move all terms containing v to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -1v = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -1v = 0 + -1 -1v = 0 + -1 Combine like terms: 0 + -1 = -1 -1v = -1 Divide each side by '-1'. v = 1 Simplifying v = 1## Solution

v = {-8, 1}

| b^2+9b+20=0 | | n^2-11n+24=0 | | x^2-13x+40=0 | | r^2-12r+35=0 | | m^2-5m=0 | | 5x^2=50 | | t^2+7t-35=2t-11 | | 2(x^2)-7x=1 | | x^2+4x-2m=0 | | 27x^2-5x=0 | | 7e^8+t=2 | | 13x^2-28x=0 | | 15n+3n^4-4n+12n^4+n= | | 2x^2-24x=-2x^2-7x-18 | | 30x^3-9x^2-3x=0 | | x^2+4=17 | | (x^3+2x+3x+6)= | | (2x^3+3)= | | (x^2+3)(x^3+2x^2+3x+6)+(2x^3+3)= | | 10y^2+33y+20=0 | | y^3+8y^2+16y=0 | | x^2+4x-60=0 | | 14x^2-5x=0 | | (x^3+y^5)(x^3-y^5)= | | 5x^2+11x+1=0 | | y^2-16y-4= | | y=5x^2-3x+5 | | 7x-28=2x^2-8x-3x+12 | | y=x^2+5x | | y=x^2+2x | | x^7-5x^5+x^2-5=0 | | 15x^2-8x-7=0 | | X^2+6x-27=0 | | 3x^2-6x+12=0 | | (4x^3-6x^2+5)-(8x^2+3x-6)= | | 11x^2-2x+9=0 | | 4x(2x^2-6x-5)= | | 10x^2+5x+8=0 | | 9x^2+9x+8=0 | | 12x^2+5x+10=0 | | 9x^2+21x+12=0 | | -2x^2+4x+12=0 | | 3x^2+10x+8=0 | | -8x^2+8x-2=0 | | X^2-x-2=0 | | 3x^2+x-1=0 | | (8x^4+5x^3-5)-(5x^2-6x+4)= | | 2x^2+10x+12=0 | | (7m^8-5m^3+9m^2+5)+(9m^7+3m^3-4m)= | | X^2-5x-48=0 | | X^2-12x+20=0 | | x^4-4x^3+5x^4-9x^3+2= | | (6x^4y^3+9x^3y^2)+(3x^3y^3-2x^3y^2-7xy)= | | y=x^3+3x^2-9x-8 | | 4x^4+3x^2-1=0 | | kx^2+4x+(5-k)=0 | | 12a^4b^3=0 | | 108x^4+360x^3+447x^2+245x+50=35 | | -35x^2-5x+30=0 | | 12x+2=3x^2 | | 2x^2+3x+5=0 | | (12x^2-3x-8)-(4x^2+5)= | | 5n+6n^4+3n-8n^4+n= | | 3n-2n^4+n+7n^4-2n= | | 12n-2n^4-10n-2n^4+n= |

- Equations solver - equations involving one unknown
- Quadratic equations solver
- Percentage Calculator - Step by step
- Derivative calculator - step by step
- Graphs of functions
- Factorization
- Greatest Common Factor
- Least Common Multiple
- System of equations - step by step solver
- Fractions calculator - step by step
- Theory in mathematics
- Roman numerals conversion
- Tip calculator
- Numbers as decimals, fractions, percentages
- More or less than - questions